Burnout Syndrome analysis among hospital nurses using Maslach Burnout Inventory - Human Service Survey (MBI-HSS): a case study. Issue 1 (September 2020) - Erwan, F; Iqbal, M; Hasanuddin, I; Zuhri, S; Maydini, C M
Abstract: Burnout is a psychology syndrome which experienced by any professions throughout their careers. This study analyses burnout syndrome encountered by hospitals' nurses based on the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) and provides findings by looking at the dimension of burnout and demographic factors which consist of sex, age, marital status, level of education, years of career, and duty station. This study reveals that; the overall value of burnout experienced by hospitals' nurses is categorized into level 1 with the highest value presented by dimension 1 (physical exhaustion), and burnout generally experienced by man, nurses younger than 30 years old, married nurses, lower degree nurses, nurses whose less than 20 years in career, and nurses whose responsible in terminal care and emergency unit. In addition, data obtained from the survey is utilized to determine burnout causative factors using fishbone and pareto diagram.